PENGARUH INDEKS GLOBAL TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) : BUKTI EMPIRIS MENGGUNAKAN DATA HARIAN - Najibullah Najibullah (Jurnal Mahasiswa Akuntansi Samudra, 2023)
This research aims to test the effect of global indeks daily movement on IHSG. The research choose S&P500 index as a global proxy and Hangseng(HSI) and Nikkei 225 (N225) as regional proxies. Using daily end of day closing data from 2015 to 2020, the study found that S&P500 index has positif and significant effect on IHSG. Meanwhile, Hangseng index is also found to have a positif and signficant effect on IHSG. On the other hand, consistent with previous finding, data used in this study is also unable to prove that there is a significant effect from Nikkei 225 indeks on IHSG